Thin film supercapacitors using a sputtered RuO2 electrode - Lim, JH; Choi, DJ; Kim, HK; Cho, WI; Yoon, YS (ELECTROCHEMICAL SOC INC, 2001)
An all solid-state thin film supercapacitor (TFSC) was fabricated with an amorphous ruthenium oxide (RuO2) thin film electrode and an amorphous LixPOyNz (Lipon) thin film electrolyte. The electrochemical behavior of the RuO2/Lipon/RuO2/Pt TFSC was characterized by a charge-discharge technique in the potential range of 0-2 V. The RuO2/Lipon/RuO2/Pt TFSC exhibited a behavior of a bulk-type supercapacitor, even though the capacity of an as-fabricated TFSC was found to be much lower than the bulk one and showed a rapid decrease in capacity. This can be explained by excess oxygen ions and interfacial structure modification. The discharge yield dropped by 53% after 500 cycles. The capacitance per volume of the RuO2/Lipon/RuO2/Pt TFSC at the first cycle is 38 mF/cm(2) mum. (C) 2001 The Electrochemical Society. All rights reserved.
Keywords: RUTHENIUM OXIDE